Factors Affecting to Self-Discipline of Students of Opportunity Expansion School in Phra Nakhon Si Ayutthaya - หลวงราช เบญญาภา (Journal of Educational Review Faculty of Education in MCU, 2018)
The purposes of this research were to 1) study the level to self-discipline of students of opportunity expansion school in Phra Nakhon Si Ayutthaya. 2) study the factors affecting to self-discipline of students of opportunity expansion school in Phra Nakhon Si Ayutthaya. and 3) study the developmental approach to self-discipline of students of opportunity expansion school in Phra Nakhon Si Ayutthaya. This research is mixed methods by used the quantitative research and qualitative research. The research the samples were 372 lower secondary school students studying in the academic year 2016 in 12 schools under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 2. Multi-stage random sampling method. There were 10 key informants administered with in-depth interviews. The research instruments were the questionnaire and in-depth interviews. The statistics used in the data analysis were frequency, percentage, mean ( ), standard deviation (S.D.), Pearson’s product-moment correlation coefficient, multiple regression analysis (stepwise) and content analysis. The results of the study revealed as follows. The self-discipline of students of opportunity expansion school in Phra Nakhon Si Ayutthaya was in the high level. The factors affecting to self-discipline of students of opportunity expansion school in Phra Nakhon Si Ayutthaya this include; The internal factors included personal attention on morality and future oriented aspect while, the family factor included support of learning from parents and the school factors were relationship among teachers and students and relationships with friends and school environment. All these six variables affected to self-discipline of students of opportunity expansion school in Phra Nakhon Si Ayutthaya at the .05 level of statistical significance.